Preparing Today’s Youth for the Changing World of Technology: The Role of Technical Education Teachers - Eke, Felix Chima (Richtmann Publishing, 2011)
In time of distress, people desire to be in tune with on-going expected technological changes, technical education hasalways come to help. This work highlights few of those moments in the developmental history of the United States of Americaand Nigeria. it also discusses expectations today’s world projection into what tomorrow’s world may look like and what rolestechnical education teachers should play for the youth to be able to face the new developments that are fast taking over orpresent ways of doing things. A few recommendations were put forward among which is making teacher education a life longexperience and the call for the engagement of serving and retired industrial workers to help in developing the technological knowhow of youths of tomorrow.